Efektivitas Kebijakan Keimigrasian dalam Pencegahan Tindak Pidana Perdagangan Orang di Indonesia - Azhari, Wiwin Windya (Indonesian Democracy Research Center, 2024)
Human trafficking remains a serious transnational crime and a persistent threat in Indonesia. This study aims to analyze the effectiveness of immigration policy in preventing human trafficking by examining its implementation and the challenges encountered. This research employs a qualitative approach through a systematic literature review, drawing on regulations, government reports, IOM data, and national as well as international journal articles. The analysis applies Van Meter and Van Horn’s policy implementation model and Soerjono Soekanto’s legal effectiveness theory. The findings indicate that Indonesia’s immigration policy provides a strong normative framework through Law No. 6 of 2011 and Law No. 21 of 2007, but its effectiveness remains partial due to limited human and technological resources, weak inter-agency coordination, and low legal awareness among communities. This study recommends strengthening the capacity of immigration institutions, integrating cross-sector data, adopting risk-profiling-based early detection technology, and implementing continuous migration literacy and community economic empowerment programs. The study concludes that the success of preventing human trafficking relies on synergy between clear regulations, professional enforcement, and legally aware communities.